The Effect of Mathematics Anxiety and Mathematics Self-Efficacy on Mathematics Academic Achievement - Hermansyah, Hermansyah; Setia Widia Rahayu; Ferryansyah; Nurfadilla (International journal of technology and education research, 2025)
The students’ mathematics achievement at SMA Negeri 2 Tarakan remains relatively low, as indicated by the documented results of their daily mathematics tests. This issue can be attributed to several factors, including mathematics anxiety and mathematics self-efficacy. This study examines the influence of mathematics anxiety and self-efficacy on the mathematics achievement of 11th-grade students at SMA Negeri 2 Tarakan, both partially and simultaneously. The research employed a quantitative ex post facto causal model. The sample consisted of 188 students, selected through cluster random sampling, with the sample size determined using the Slovin formula. The research instruments included questionnaires measuring mathematics anxiety and self-efficacy and documenting the students’ mathematics achievement. The collected data were analyzed using descriptive and inferential statistics with the help of Jamovi software. The partial analysis results showed that mathematics anxiety significantly negatively affected students’ mathematics achievement, with the obtained linear regression equation being . Additionally, mathematics self-efficacy significantly positively affected students’ mathematics achievement, with the linier regression equation being . Simultaneously, the analysis revealed that mathematics anxiety and mathematics self-efficacy had a significant combined effect on students’ achievement, accounting for 24.8% of the variance, with the multiple linear regression equation being . Based on the analysis, it can be concluded that both mathematics anxiety and self-efficacy significantly influence students’ mathematics achievement, individually anf collectively.